Reduced Bone Mineral Density Is Associated with Celiac Disease Autoimmunity in Children with Type 1 Diabetes - Simmons, Kimber (J Pediatr, 2015)
OBJECTIVE: To evaluate the association between bone mineral density (BMD), glycemic control (HbA1c) and celiac autoimmunity in children with type one diabetes (T1D) and in an appropriate control population. STUDY DESIGN: BMD was assessed cross-sectionally in 252 children with T1D (123 positive for TG and 129 matched children who were negative for transglutaminase [TG]). Additionally, BMD was assessed in 141 children without diabetes who carried T1D-associated HLD-DR,DQ genotypes (71 positive for TG and 70 negative). RESULTS: Children with T1D who were positive for TG had significantly worse BMD L1-L4 z-score compared with children with T1D who were negative for TG (−0.45 ± 1.22 vs. 0.09 ± 1.10, p=0.0003). No differences in growth measures, urine N-telopeptides, vitamin D 25OH, ferritin, TSH or HbA1c were found. However, both higher HbA1c (β= −1.25 ± 0.85, p=0.0016) and TG (β= −0.13 ± 0.05, p = 0.0056) were significant and independent predictors of lower BMD in multivariate analyses. No differences in BMD or other variables measured were found between children without diabetes who were positive versus negative for TG. CONCLUSIONS: The results suggest a synergistic effect of hyperglycemia and celiac autoimmunity on low BMD.